2014
DOI: 10.1186/1471-2164-15-130
|View full text |Cite
|
Sign up to set email alerts
|

The CtrA phosphorelay integrates differentiation and communication in the marine alphaproteobacterium Dinoroseobacter shibae

Abstract: BackgroundDinoroseobacter shibae, a member of the Roseobacter clade abundant in marine environments, maintains morphological heterogeneity throughout growth, with small cells dividing by binary fission and large cells dividing by budding from one or both cell poles. This morphological heterogeneity is lost if the quorum sensing (QS) system is silenced, concurrent with a decreased expression of the CtrA phosphorelay, a regulatory system conserved in Alphaproteobacteria and the master regulator of the Caulobacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
72
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(75 citation statements)
references
References 55 publications
2
72
0
1
Order By: Relevance
“…So far, CtrA was shown to control motility in all Alphaproteobacteria in which it was tested (Wu and Newton, ; Lang and Beatty, ; Miller and Belas, ; Belas et al ., ; Greene et al ., ; Zan et al ., ; De Nisco et al ., ; Wang et al ., ). Our data suggest that CtrA is the master regulator of flagella synthesis in S. melonis , initiating a cascade of regulation that involves σ 54 and the σ 54 ‐dependent regulator FleT for the regulation of class III genes, and FliA for class IV flagellin genes (Fig E).…”
Section: Discussionmentioning
confidence: 97%
“…So far, CtrA was shown to control motility in all Alphaproteobacteria in which it was tested (Wu and Newton, ; Lang and Beatty, ; Miller and Belas, ; Belas et al ., ; Greene et al ., ; Zan et al ., ; De Nisco et al ., ; Wang et al ., ). Our data suggest that CtrA is the master regulator of flagella synthesis in S. melonis , initiating a cascade of regulation that involves σ 54 and the σ 54 ‐dependent regulator FleT for the regulation of class III genes, and FliA for class IV flagellin genes (Fig E).…”
Section: Discussionmentioning
confidence: 97%
“…However, there is notable diversity in the transcriptional output of this system across the clade (10)(11)(12)(13), which likely reflects the breadth of niches inhabited by these species (14). The function of this system in Brucella abortus, which is capable of infecting, growing, and replicating inside mammalian cells, is poorly understood, although previous studies of Brucella CtrA have revealed a possible role in the control of cell division (15).…”
mentioning
confidence: 99%
“…Our results show that a single mutation in CckA is able to turn on the Fla2 system and imply that the proteins homologous to CtrA and ChpT should be involved in this phenomenon. The idea that CtrA and ChpT could also control the expression of the Fla2 genes is based on the fact that these proteins together with CckA are implicated in the expression of the flagellar genes in other bacteria (14)(15)(16)(17)(18)(19). Therefore, we searched the genome of R. sphaeroides for genes encoding these proteins and found that RSWS8N_03320 (RSP_2621 in 2.4.1) encodes the response regulator CtrA, whereas RSWS8N_16219 (RSP_3825) encodes the homologue of the phosphotransfer protein ChpT.…”
Section: Resultsmentioning
confidence: 99%
“…In this group of bacteria, there is no evidence regarding the control of the activity of CckA, but it has been reported that the expression of cckA, chpT, and/or ctrA is reduced in quorum sensing mutants in Ruegeria sp. strain KLH11, Dinoroseobacter shibae, and Rhodobacter capsulatus (16,17,19,20). However, in Ruegeria sp.…”
mentioning
confidence: 97%
See 1 more Smart Citation